Egypt's military council : between a rock and a hard place - James M. Dorsey (2012)
The Egyptian armed forces, revered before the popular revolt that ousted President Hosni Mubarak, took power in February with a pledge to lead the country to free and fair elections within six months. It has since stumbled from crisis to crisis and extended the period for a handover of power to 2013.